Intra-cultural Communication in Barong Burutuk performance in Truyan Village, Kintamani District, Bangli District - Lio, Ulio; Dharma, I Wayan Yudhasatya (UHN IGB Sugriwa Denpasar, 2025)
Barong Burutuk staging is one form of sacred tradition performed by the people of Trunyan Village to honor and glorify their supreme god called Ratu Sakti Pancering Jagat. The staging process requires a variety of communication, interaction, ethics and also special and distinctive tools and the same understanding in interpreting the tradition of barong burutuk dance. Intra-cultural communication is established in the barong brutuk dance performance through interaction between people who certainly have the same understanding of the values, norms, beliefs, and communication processes in the barong burutuk dance performance. This type of research is a qualitative research that describes and interprets the object of research in the field of Barong Burutuk dance performance in Truyan Village. Starting from the description of the discussion, it can be concluded that Barong Burutuk Dance is a sacred dance (wali) that is offered in the Full Moon Ceremony of kapat Lanang, Sasih Kapat where at that time it was a long dry season, so that efforts arose from Pakraman Truyan village to ask for natural fertility. The necessary equipment or means is a barong Brutuk dance costume made of Keraras, namely dried banana leaves, white clay powder, rice flour and fragrant oil. And the procedure for staging is staged at the peak of the ceremony precisely on the eighth and ninth days. Barong Burutuk dance performance aims to build a more harmonious relationship between people and nature, one of which is to ask for fertility and maintain the tradition of local cultural values.